Climate-smart agriculture for greenhouse mitigation sustainable intensification and ensuring farmers’ income - Somasundaram, J.; Sinha, N. K.; Mohanty, M.; Chaudhary, R. S.; Bharti, K.; Patra, A. K. (Indian Farming, 2018)
The climate-smart agriculture aims to improve food security, help communities adapt to climate change and also contributes to mitigation of climate change effects by adopting appropriate practices, developing enabling policies and institutions and mobilizing needed finances. It also strengthened food security and delivered environmental benefits. Moreover, ecosystem-based approaches such as conservation agriculture, integrated nutrient and soil management, mulch cropping, cover cropping, alterations in cropping patterns and rotations, crop diversification, using high quality seeds and planting materials of adapted varieties, integrated pest and weed management, grasslands management, water and irrigation management, and organic agriculture. Besides, climate-smart agriculture helped to overcome as well as cope-up with climatic vulnerabilities such as drought, prolonged dry-spell, water-logging, floods etc. The climate-smart agriculture related interventions helped farmers to face the climate vulnerability–more ‘smartly, swiftly and successfully’ in minimize losses due to climate aberration.